2013
DOI: 10.1063/1.4812832
|View full text |Cite
|
Sign up to set email alerts
|

On the hydrodynamic interaction between a particle and a permeable surface

Abstract: The motion and deposition of a particle translating perpendicular to a rigid, permeable surface is considered. The lubrication approximation is used to derive an equation for the pressure in the gap between the particle and the permeable surface, with a symmetric shape prescribed for the particle. The hydrodynamic force on a particle is, in general, a function of the particle size and shape, the distance from the surface and the surface permeability, and its sign depends on the relative motion of the particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…The permeation velocity through the membrane is V 0 and λ D is the Debye length. pressure within the thin fluid film, separating the droplet and the membrane, as 14,15…”
Section: Problem Formulation Geometry and Long-wave Approximationmentioning
confidence: 99%
“…The permeation velocity through the membrane is V 0 and λ D is the Debye length. pressure within the thin fluid film, separating the droplet and the membrane, as 14,15…”
Section: Problem Formulation Geometry and Long-wave Approximationmentioning
confidence: 99%
“…The initial minimum fluid layer thickness is denoted by h min (0) = H f (> 0). Following Stone 10 , Skotheim and Mahadevan 17 and Ramon et al 15 , we consider smooth axisymmetric shapes of the form…”
Section: Model Formulationmentioning
confidence: 99%
“…Wu 11 (see also Prakash and Vij 12 and the review by Wu 4 ) considered squeeze-film flow between two annular discs, one of which is coated with a porous layer, and found that increasing the permeability of the layer reduces the normal force on the discs. Goren 13 and Nir 14 (see also the summary of previous work given in Table 1 in Ramon et al 15 ) calculated the force required to pull a sphere away from contact with a thin porous membrane at a constant velocity, and found that, unlike in the case of an impermeable membrane, the force is finite. In particular, Goren 13 found that the maximum value of the force does not occur when the sphere and the membrane are in contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 On the other hand, the velocity slip also occurs in porous media such as the brine water and supercritical CO 2 flow in nanopores of sandstone rocks, and it is necessary to consider the SBC for the fluid flow in microporous media. [25][26][27][28][29][30][31] In addition, we compare the fluid flow past the porous wall with the one past a rough wall. Much work has been done to study the influence of wall roughness on the channel flows, including the rectangular, sinusoidal, triangular [32][33][34] and topological surfaces.…”
Section: Introductionmentioning
confidence: 99%